Features of the Philosophical and Ethical Interpretation of the Concepts of Crime and Punishment (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
The relationship between the concepts of crime and punishment was considered in philosophical teachings as socio-ethical categories even in ancient times. Since without a philosophical understanding of the crime and its causes it is difficult to understand the meaning and essence of punishment. In turn, the philosophical and ethical interpretation of these concepts became the basis for their introduction into legal science. This article examines the conceptual and theoretical aspects of the philosophical understanding of the concepts of crime and punishment.